Caste and its histories in colonial India: a reappraisal - O'Hanlon, R (Cambridge University Press, 2017)
David Washbrook's influential early work on South India set the terms for much subsequent debate about caste, with its exploration of the key role of the colonial state in shaping caste ideologies and institutions. Over subsequent decades, historians and anthropologists have come increasingly to emphasise the ‘colonial construction’ of caste and its enduring legacies in post-colonial India. Yet there were also significant continuities linking the forms of colonial caste with much earlier regional histories of conflict and debate, whose legacies can be traced into the late colonial period. In particular, the juxtaposition between Brahman and non-Brahman itself was anticipated in a tradition of conservative social commentary that emerged in the Deccan Sultanate state of Ahmadnagar, and came to circulate widely through Banaras and western India during the seventeenth and eighteenth centuries. This tradition of commentary acquired new salience during the nineteenth century. It entered the colonial archive as an authoritative source of knowledge, and also provoked early ‘non-Brahman’ intellectuals into a fresh engagement with its conservative social vision. In their attempts to rebut this vision, these intellectuals displayed a detailed knowledge of its social history and a deep familiarity with the judicial decisions through which it had been upheld in earlier centuries.